Cyclic fatigue of two different single files with varying kinematics in a simulated double‐curved canal. Issue 3 (3rd May 2015) - Neelakantan, Prasanna; Reddy, Pallavi; Gutmann, James L.
Abstract: Objective: To evaluate and compare the cyclic fatigue of a rotary (One Shape) and reciprocating (Reciproc) single file system in a simulated S‐shaped canal in static and dynamic models. Methods: The instruments ( n  = 50 per instrument) were tested in a custom‐made device under static ( n  = 25) and dynamic loads ( n  = 25) to determine the number of cycles to fracture (NCF). The length of the fractured segments was also measured. Cyclic fatigue data were analyzed by one‐way analysis of variance and Tukey honestly significantly different tests, while the data recorded for the fractured fragment lengths were compared using Student's t ‐test with the level of significance set at 0.05. Results: The fatigue life of Reciproc was significantly higher in the static (coronal curvature: 717.60 ± 45.32 NCF; apical curvature: 621.80 ± 60.15 NCF) and dynamic models (coronal curvature: 972.40 ± 54.30 NCF, apical curvature: 897.70 ± 47.10 NCF) as compared with One Shape ( P  < 0.05). The fatigue life was significantly prolonged in the dynamic model for Reciproc ( P  < 0.05) as compared to One Shape ( P  > 0.05). Conclusion: The results of the present study showed that the single file reciprocating system (Reciproc) had a longer fatigue life than the single file rotary system (One Shape).